2018
DOI: 10.1093/abm/kay059
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences in Tobacco Control Research Findings From Convenience and Probability Samples

Abstract: Using MTurk convenience samples can yield generalizable findings for experiments and observational studies. Prevalence estimates from MTurk convenience samples are likely to be over- or underestimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 24 publications
3
80
0
2
Order By: Relevance
“…Finally, while the online sample was designed to reflect the diversity of the Colombian population, individuals with low literacy, less than a high school diploma, or lack of access to the internet were less likely to be included in this online panel. On the other hand, previous research has suggested that online convenience samples can lead to generalizable findings for experiments [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while the online sample was designed to reflect the diversity of the Colombian population, individuals with low literacy, less than a high school diploma, or lack of access to the internet were less likely to be included in this online panel. On the other hand, previous research has suggested that online convenience samples can lead to generalizable findings for experiments [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Online convenience samples are a quick and low-cost way to study health behaviour and can yield highly generalisable findings for experiments. 28 Participants were current e-cigarette users (defined as currently vaping every day or some days 29 ), current smokers (defined as having smoked at least 100 cigarettes and now smoking every day or some days 30 31 ) or dual users (defined as a current e-cigarette user and current smoker). Recruitment occurred through Amazon's Prime Panels, a platform with access to over 20 million participants for behavioural research.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Because the use of convenience samples, such as MTurk, can raise questions about generalizability, recent research has investigated the correspondence between experimental results obtained from MTurk and other samples (see Berinsky, Huber, and Lenz ). Research comparing treatment effects from experiments conducted with population‐based samples to those from experiments conducted in MTurk generally shows high levels of correspondence (see Coppock ; Coppock, Leeper, and Mullinix ; Jeong et al ; Mullinix et al ). There is also evidence that liberals and conservatives on MTurk share the views of their ideological counterparts in the U.S. population (Clifford, Jewell, and Waggoner ).…”
Section: Survey Experimentsmentioning
confidence: 99%